SIMILARITIES AND DIFFERENCES OF GRAMMATICAL CATEGORY GENDER IN ENGLISH AND UZBEK LANGUAGES - Maxmutova Aqilay Baxitjanovna (PEDAGOGS, 2024)
Annotation: This article provides a comparative analysis of the grammatical category of gender in English and Uzbek languages, highlighting both similarities and differences. It explains that while English employs a system of natural gender with specific pronouns (“he,” “she,” “it”) and some gendered nouns, Uzbek lacks grammatical gender entirely, using the same pronoun (“u”) for all genders and making no gender distinctions in nouns or adjectives. The article discusses how English is evolving towards gender-neutral language to promote inclusivity, whereas Uzbek’s inherent gender neutrality simplifies its grammatical structure. Cultural and linguistic implications of these differences are also explored, emphasizing how language can reflect and influence societal views on gender.